A Novel Graphene-Based Nanomaterial Modified Electrochemical Sensor for the Detection of Cardiac Troponin I - Li, Jing; Zhang, Shenwei; Zhang, Li; Zhang, Yu; Zhang, Hua; Zhang, Chuanxi; Xuan, Xuexi; Wang, Mingjie; Zhang, Jinying; Yuan, Yiqiang (Frontiers in Chemistry, 2021)
Acute myocardial infarction has a high clinical mortality rate. The initial exclusion or diagnosis is important for the timely treatment of patients with acute myocardial infarction. As a marker, cardiac troponin I (cTnI) has a high specificity, high sensitivity to myocardial injury and a long diagnostic window. Therefore, its diagnostic value is better than previous markers of myocardial injury. In this work, we propose a novel aptamer electrochemical sensor. This sensor consists of silver nanoparticles/MoS2/reduced graphene oxide. The combination of these three materials can provide a synergistic effect for the stable immobilization of aptamer. Our proposed aptamer electrochemical sensor can detect cTnl with high sensitivity. After optimizing the parameters, the sensor can provide linear detection of cTnl in the range of 0.3 pg/mL to 0.2 ng/mL. In addition, the sensor is resistant to multiple interferents including urea, glucose, myoglobin, dopamine and hemoglobin.